1994
DOI: 10.1161/01.cir.90.4.1706
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function at 3 months after successful thrombolysis. Impact of reocclusion without reinfarction on ejection fraction, regional function, and remodeling.

Abstract: BACKGROUND After successful thrombolysis for acute myocardial infarction, reocclusion is observed in about 30% of patients after 3 months and usually occurs without reinfarction. We studied the impact of reocclusion without reinfarction on global and regional left ventricular function and on remodeling during that period. METHODS AND RESULTS The patients for this analysis constituted a subset of those enrolled in the APRICOT-trial, which was designed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 30 publications
(4 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, patients without reocclusion dem-L eft ventricular remodeling after acute myocardial infarction, resulting in enlargement of the ven tricle, is a progressive process beginning in the early phase and continuing for months and years.1 -4 It occurs predominantly after a large transmural anterior wall infarction2* 5 and carries an adverse prognosis.6* 7 There are supporting experimental and clinical data that successful reperfusion of the infarct-related artery can prevent this sequela by limiting infarct expansion. [8][9][10] Re cent clinical studies have shown that infarct-related artery patency is one of the most important determinants for ventricular remodeling after myocardial infarction.4*1 U2 Initial success of thrombolysis, however, is followed by reocclusion in almost 30% of patients within 3 months after myocardial infarction.13*14 Reocclusion is associated with a more complicated hospital course,15 impaired short-term recovery of regional and global ventricular function, [15][16] and an increase in end-systolic volume 3 months after myocardial infarction. 16 Long-term data with respect to reocclusion are limited.17 Therefore, the aim of this study was to determine the implications of reocclusion on left ventricular size and function 5 years after first anterior myocardial infarction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients without reocclusion dem-L eft ventricular remodeling after acute myocardial infarction, resulting in enlargement of the ven tricle, is a progressive process beginning in the early phase and continuing for months and years.1 -4 It occurs predominantly after a large transmural anterior wall infarction2* 5 and carries an adverse prognosis.6* 7 There are supporting experimental and clinical data that successful reperfusion of the infarct-related artery can prevent this sequela by limiting infarct expansion. [8][9][10] Re cent clinical studies have shown that infarct-related artery patency is one of the most important determinants for ventricular remodeling after myocardial infarction.4*1 U2 Initial success of thrombolysis, however, is followed by reocclusion in almost 30% of patients within 3 months after myocardial infarction.13*14 Reocclusion is associated with a more complicated hospital course,15 impaired short-term recovery of regional and global ventricular function, [15][16] and an increase in end-systolic volume 3 months after myocardial infarction. 16 Long-term data with respect to reocclusion are limited.17 Therefore, the aim of this study was to determine the implications of reocclusion on left ventricular size and function 5 years after first anterior myocardial infarction.…”
mentioning
confidence: 99%
“…[8][9][10] Re cent clinical studies have shown that infarct-related artery patency is one of the most important determinants for ventricular remodeling after myocardial infarction.4*1 U2 Initial success of thrombolysis, however, is followed by reocclusion in almost 30% of patients within 3 months after myocardial infarction.13*14 Reocclusion is associated with a more complicated hospital course,15 impaired short-term recovery of regional and global ventricular function, [15][16] and an increase in end-systolic volume 3 months after myocardial infarction. 16 Long-term data with respect to reocclusion are limited.17 Therefore, the aim of this study was to determine the implications of reocclusion on left ventricular size and function 5 years after first anterior myocardial infarction.…”
mentioning
confidence: 99%
“…These may include reduction of ventricular remodeling, decreased ventricular instability with the resulting diminished incidence of ventricular arrhythmias, and provision of collateral vessels to other territories in the event of further coronary artery occlusion [5][6][7][8][9][10]. In addition to promoting an acute inflammatory response and local edema, reperfusion of IRA with an adequate blood flow at a proper arterial perfusion pressure increases tissue turgor, which may have a scaffolding further reinforced by other reported studies [21][22][23][24][25]. These latter investigations demontrated that late patency of an IRA seems to have a positive influence on remodeling and survival and that this effect is independent of any acute reduction of infarct size secondary to reperfusion during the acute phase of an evolving AMI.…”
Section: Editorialmentioning
confidence: 94%
“…Analogous to that finding, a reduced risk of reocclusion may not automatically confer improved outcome, especially in a low-risk population. Besides the adverse impact on long-term survival, reocclusion also impairs left ventricular recovery [15]. The lower reocclusion rate in smokers may therefore confer a beneficial effect on remodeling and a lower risk to develop heart failure.…”
Section: Smoking and Clinical Outcomementioning
confidence: 99%
“…Notably, most reocclusions occur without clinical reinfarction [12][13][14]. Even in these cases, reocclusion has adverse impact on recovery of left ventricular function [15]. Previously we have shown that reocclusion is a strong predictor of 10-year cardiac mortality, independent of left ventricular ejection fraction, and even when presenting without signs of reinfarction or recurrent ischemia [16].…”
Section: Introductionmentioning
confidence: 99%